A Systematic Review of Research Trends on the Culturally Responsive Transformative Teaching (CRTT) Model in Science Learning - Annisa Mujriati; Dini Astuti (Contextual Natural Science Education Journal, 2025)
This study conducted a systematic review of research trends on the Culturally Responsive Transformative Teaching (CRTT) model in science learning in the period 2016–2025. The methods used include collecting bibliometric data from Google Scholar assisted by the Publish or Perish and Dimensions.ai applications, as well as visualization analysis using VOSviewer to map the number of publications, distribution of document types, disciplines, keyword frequency, and keyword relationships and densities. The results show a sharp increase in the number of publications since 2020, with a peak in 2024, reflecting the increasing attention to the integration of culture and local wisdom in science education. Journal articles are the main media (55 publications), followed by edited books, chapters, proceedings, and monographs. The fields of Education and Curriculum and Pedagogy dominate the literature, while language and cultural studies have a high citation impact. Keyword analysis emphasizes the focus on the implementation of CRTT at the high school level, integration with Problem-Based Learning and local wisdom, as well as aspects of evaluation and methodology. Network, overlay, and density visualizations demonstrate the progression from theoretical concepts to transformative applied practices. Further research is recommended to explore the integration of technology, ethnoscience, and cross-disciplinary approaches to enrich CRTT implementation.